Building Fantasies About University Extension in the Student Population of the National University of Costa Rica - Alfaro Salas, Marly Yisette (2019)
The present work systematizes some of the frequencies generated within the framework of the Methodological Innovation Program, student participation, and knowledge management of the School of International Relations at the National University of Costa Rica on student perceptions about university extension. These frequencies were obtained by applying Likert and Tourstone scales with a Cronbach alpha of .902 and n in 917 cases. The presence of two symptoms associated with how ideas about university extension are ideologically transmitted is visualized as a fundamental finding, where there is an approach responding to models of awareness, but, in everyday actions, altruistic and conservative tendencies are reflected. The importance of religious and educational organizations without formal political dyes is established as a space for linking young people, and questions about the university’s behavior in the field of guaranteeing respect for diversity without forgetting social justice.